The European Political Community: The Advancement of EU influence and its Impact on Enlargement - Griessler, Christina Eva (International Problems, 2026)
The author analyses the European Political Community (EPC) as a political platform of European states, including the EU and other partners from the EU’s wider European neighbourhood, aiming to jointly address issues of security, energy, and mobility, and a strategic foreign policy alignment. With the launch of the EPC in 2022, the argument was put forward that it could become an opportunity for giving the EU enlargement process renewed impetus by addressing the main obstacles to EU accession during informal meetings. Since Russia’s invasion of Ukraine in February 2022 and the start of Donald Trump’s second presidency of the US in 2025, the EU has faced external upheaval and new challenges. Two main questions are addressed. Firstly, is the EU using the EPC to influence partners to underline the EU’s role as an efficient foreign political actor? The second question relates to the idea that the EPC might be a useful tool to generate progress on EU enlargement, especially since political leaders from the candidate countries participate in the EPC’s meetings. The paper assesses the EU’s foreign policy role and the EU’s norm transfer capability within the EPC. The concepts of EU normative power, its strategic approach of external governance and the ideas of functional cooperation to initiate another push the accession to the EU of the Western Balkan countries are discussed in the context of the EU’s weakening actorness, which negatively impacts candidate countries’ motivation to fulfil EU conditionality. The paper suggests that the EPC is not a suitable tool to strengthen the EU’s role, as it lacks the political standing to prove that it is a reliable and credible partner for the Western Balkan countries and even for the Association Trio (Georgia, Moldova and Ukraine).
Keywords: European Union; Accession; Foreign Policy; Governance; Europeanisation; Western Balkans; Eastern partners